THE ROLE OF KINETIC METHODS USED IN DUPUYTREN DISEASE - Oana Berăriţa; Maria Daniela Crăciun (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
The Dupuytren disease is a flexion contraction that usually develops along the years and manifests through the thickening of the hand skin, the fingers can be also affected, especially the metacarpophalangeal joints and the proximal interphanageal joint. The majority of the patients suffering from Dupuytren disease are males over the age of fifty, being diagnosed with the bending contraction of the fingers, a major incapacity of using the hand, the capacity of "grabbing" being highly affected. An important means of treating this disease is kinetic therapy/ physical therapy that can be used before and after surgery in order to maintain and increase the functionality of the hand from both muscular and articular point of view.